The state of the fishery, conservation and management of the stalked barnacle Pollicipes pollicipes in Portugal - Cruz, T (2016)
The stalked barnacle Pollicipes pollicipes is the most important intertidal economical resource in Portugal. The assessment of the state of the fishery, conservation and management of P. pollicipes in Portugal was made for the first time in three regions with different regulations regarding this fishery: two marine protected areas (“Reserva Natural das Berlengas”, RNB; and “Parque Natural do Sudoeste Alentejano e Costa Vicentina”, PNSACV); and the Center coast. Different approaches (independent observations, inquiries, logbooks) and sources of data (past and recent) were used. An overall negative tendency of the state of the fishery and conservation of this resource was observed in all regions, with the exception of the stable tendency detected in PNSACV when using the inquiries approach. A weak management was considered to be in practice at Center and at PNSACV, while an acceptable management was inferred for RNB. We recommend a change into a co-management system that should be tested in pilot regions as RNB and/or PNSACV.